The Effect Of Warm Breast Compresson Colostrum Expenditure In Primigravid Mothers - Turnip, Meria; Yuningsih, Lisma; Pardede, Desika Wali; Siregar, Wilda Wahyuni (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Colostrum is a newborn's first food which is very important for the newborn's antibodies against bacteria, germs and viruses. Colostrum can play a role in protecting the baby's body from infections and bacteria because colostrum contains immunoglobulin substances. Applying warm compresses to the breasts can facilitate colostrum production. Warm compresses will increase blood circulation in the breasts so that oxytocin production will also increase and make colostrum production smoother. This study aims to determine the effect of warm breast compresses on colostrum production in primigravida mothers at the Saumi Midwife Clinic, Trading City. This research uses a quasi-experimental research design with a one group pretest posttest design. The population in this study were all primigravida mothers who visited the Saumi Midwife Clinic in Trading City. Sampling in this study used a purposive sampling technique based on inclusion and exclusion criteria of 15 samples. Data analysis used the Wilcoxon Signed Ranks Test. Based on the research results, it was found that there was an effect of warm breast compresses on colostrum production in primigravida mothers with a p-value =0.004